2021
DOI: 10.3758/s13415-021-00883-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between lifetime stress exposure and the error-related negativity (ERN) differ based on stressor characteristics and exposure timing in young adults

Abstract: Life stress increases risk for multiple forms of psychopathology, in part by altering neural processes involved in performance monitoring. However, the ways in which these stress-cognition effects are influenced by the specific timing and types of life stressors experienced remains poorly understood. To address this gap, we examined how different social-psychological characteristics and developmental timing of stressors are related to the error-related negativity (ERN), a negative-going deflection in the event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 177 publications
1
15
0
Order By: Relevance
“…Repeated application of tDCS may be required to induce marked and sustained effects on error monitoring and possibly reduce symptom severity. Even though previous findings suggest that modulation of neural correlates of error monitoring could be of relevance to the treatment of OCD or may impact psychological mechanisms that increase risk for psychopathology ( Banica et al, 2021 , Riesel et al, 2021 , Sildatke et al, 2022 ), more research is needed to evaluate the therapeutic relevance of ERN modulation. Thus, an avenue for future research is to examine whether long-lasting changes in the ERN can be induced (e.g., by repeated tDCS application), and to what extent modulating the ERN may relate to subsequent change at the symptom level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated application of tDCS may be required to induce marked and sustained effects on error monitoring and possibly reduce symptom severity. Even though previous findings suggest that modulation of neural correlates of error monitoring could be of relevance to the treatment of OCD or may impact psychological mechanisms that increase risk for psychopathology ( Banica et al, 2021 , Riesel et al, 2021 , Sildatke et al, 2022 ), more research is needed to evaluate the therapeutic relevance of ERN modulation. Thus, an avenue for future research is to examine whether long-lasting changes in the ERN can be induced (e.g., by repeated tDCS application), and to what extent modulating the ERN may relate to subsequent change at the symptom level.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ERN enhancement is considered a biomarker for OCD and anxiety disorders ( Gillan et al, 2017 , Riesel, 2019 ). Moreover, the ERN has been shown to be predictive of later development of anxiety disorders ( Meyer et al, 2015 , Meyer et al, 2018 ), suggesting associations with psychological risk mechanisms that render individuals more sensitive to psychosocial stressors and increase risk for psychopathology ( Banica et al, 2021 , Riesel et al, 2021 ). Thus, considering its direct relation to a probable risk mechanism in the pathogenesis of OCD and anxiety disorders, the ERN may be a suitable target for novel intervention and prevention approaches ( Meyer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we examine the relationship between interpersonal dependent and non‐interpersonal stressful life events and the ∆ERN in a sample of child and adolescent females, finding that more frequent interpersonal dependent stressors predict a larger ∆ERN (Mehra & Meyer, in press). Previous work found that higher numbers of adverse childhood experiences related to a larger ERN (Lackner et al, 2018; Wu et al, 2021) and one study found that social‐evaluative stress during early adolescence was related to an enhanced ERN (Banica et al, 2021). Moreover, two studies have found that the ERN interacts with stressful events to predict changes in anxiety prospectively (Banica et al, 2020; Meyer, Danielson, et al, 2017).…”
Section: Factors That Shape the Ernmentioning
confidence: 98%
“…The term ‘psychological vulnerability’ is herein applied to refer to the susceptibility of developing psychopathological symptoms. Psychological vulnerability in general comprises a complex variety of variables, including genetic predispositions ( Cross-Disorder Group of the Psychiatric Genomics Consortium, 2013 ), biological factors ( Labonte & Turecki, 2010 ), early environmental conditions ( Nelson et al, 2020 ), cultural and socioeconomic variations ( Dressler et al, 2008 ), the presence of external stressors ( Banica et al, 2021 ; Heim & Binder, 2012 ), the ways in which individuals cope with stressors ( Kalial et al, 2020 ; Sheffler et al, 2019 ), and interactions between such variables ( Heim & Binder, 2012 ). Hence, in working towards a comprehensive understanding of vulnerable individuals in the COVID-19 era, insights about distinct risk factors, pandemic stressors, coping strategies, and psychological health should be addressed in tandem.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the complex nature of psychological vulnerability ( Banica et al, 2021 ; Heim & Binder, 2012 ; Labonte & Turecki, 2010 ) and the compounding nature of the pandemic, there appears to be no study that has examined how previous exposure to childhood adversity and trauma and distinct pandemic stressors relate in vulnerable individuals. Disentangling the COVID-19 pandemic and its stressors is essential to identify avenues for preventing and alleviating further escalation of psychological difficulties in this at-risk group.…”
Section: Introductionmentioning
confidence: 99%